Seasonal Reproduction in Neotropical Rainforest Mammals - Dubost, Gérard (Zool Stud, 2017)
Gérard Dubost, and Olivier Henry (2017) Seasonal changes in tropical forests have been documented in dry and semi-deciduous forests, but not in evergreen ones. Owing to its high level of annual rainfall, French Guiana is considered to be a rainy region, despite a pronounced dry season. French Guiana is therefore appropriate for studying the impact of the dry season on the phenology of rainforest animals. For this purpose, the reproductive characteristics of six terrestrial mammals of the French Guiana rainforest were studied during the four main seasons of the year. Reproduction was more or less continuous in both sexes of all species. Seasonality was not very pronounced and the species were not synchronised, except in terms of births. In all species, the minimum number of litters occurred between August and October. Furthermore, the seasonal birth percentages appeared to be linked to environmental factors such as rainfall and fruiting trees, and to diet as well: the more the diet of one species was composed of fruits, the more seasonal its litters were. Thus, like in many other regions worldwide, most births occur during the most favourable seasons for raising young in this rainforest. This signi es that even in this seemingly aseasonal region, the reproduction of mammals is mainly regulated by environmental factors at the time of birth.